2019
DOI: 10.3390/su11236872
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Economic Analysis of Tropical Building Envelope Material in Compliance with Thailand’s Building Energy Code

Abstract: The building envelope has a direct impact on the overall energy consumption of a building. Thus, an improvement in the building envelope using energy-efficient material can yield the desired energy performance. This study is based on the materials and compositions used in building envelopes in compliance with the building energy code of Thailand. The building under study is an educational building located in Bangkok, Thailand. Both the energy and the economic aspects of retrofitted building envelopes are discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Saad and Kamal [74] and Chiradeja and Ngaopitakkul [23] have demonstrated that the usage of agricultural waste fibres as roof insulation could reduce heat transfer into the building and maintain a comfortable temperature inside the building space. Thus, it can help to overcome the discomfort of homes and reduce indoor electricity consumption, which enables cost savings and reduces gas production that directly pollutes the environment [20].…”
Section: Roof Insulation Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saad and Kamal [74] and Chiradeja and Ngaopitakkul [23] have demonstrated that the usage of agricultural waste fibres as roof insulation could reduce heat transfer into the building and maintain a comfortable temperature inside the building space. Thus, it can help to overcome the discomfort of homes and reduce indoor electricity consumption, which enables cost savings and reduces gas production that directly pollutes the environment [20].…”
Section: Roof Insulation Materialsmentioning
confidence: 99%
“…As a result, the temperature became lower and increased the comfort of the occupants inside. Studies showed that energy efficiency could be achieved by designing suitable roof insulation material, which depends on the local climate [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Some articles have studied building envelope design from its energy-saving potential, environmental consequences, and social impacts. It is of the utmost importance to optimize the balance between the cost and energy savings [25,26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is basically the average heat transfer rate of the building envelope material. In general, good building materials have a low transmittance value (U-value), thus giving a low OTTV value to the building [8]. Regional regulations require a maximum OTTV building value of 35 W / m2 [9].…”
Section: Figure 1 Framework Of Design Approachmentioning
confidence: 99%